2020
DOI: 10.1590/s1678-3921.pab2020.v55.01592
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric indices for the selection of hybrid citrus as rootstocks grafted with 'Valência' sweet Orange

Abstract: The objective of this work was to evaluate five nonparametric selection indices for the selection of hybrid citrus rootstocks grafted with 'Valência' sweet orange, using horticultural traits relevant for the juice processing industry. Forty-six rootstocks were evaluated in a randomized complete block design, with three replicates and five trees in the plot, in the period from 2009-2015, in a rainfed cultivation. The means of the variables plant height, accumulated fruit yield, fruit yield efficiency, total sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Focused studies were conducted to map quantitative trait loci (QTL) in citrandarins associated with host response to infection by CLas ( Soratto et al, 2020 ) and Phytophthora parasitica ( Lima et al, 2018 ), and to identify mechanisms of tolerance to HLB ( Curtolo et al, 2020 ). A series of non-parametric indices were evaluated for selection of superior hybrid rootstocks, and a ranking index was identified as the most useful for selecting productive and drought-tolerant rootstocks ( Costa et al, 2020a ).…”
Section: History Of Citrus Rootstocks and Breedingmentioning
confidence: 99%
“…Focused studies were conducted to map quantitative trait loci (QTL) in citrandarins associated with host response to infection by CLas ( Soratto et al, 2020 ) and Phytophthora parasitica ( Lima et al, 2018 ), and to identify mechanisms of tolerance to HLB ( Curtolo et al, 2020 ). A series of non-parametric indices were evaluated for selection of superior hybrid rootstocks, and a ranking index was identified as the most useful for selecting productive and drought-tolerant rootstocks ( Costa et al, 2020a ).…”
Section: History Of Citrus Rootstocks and Breedingmentioning
confidence: 99%
“…Although the specific Picos 2014 trial contains only 45 of the 350 hybrids in the mapping population, the observed significant rootstock effects on a broad range of measured traits, high heritability (h 2 ) of many important traits, and strong association of particular parental combinations with particular trait combinations suggest that the strategy will be effective. Ranking indices to use for systematic selection of superior citrus rootstocks in trials have been described ( Costa et al., 2020a ), and provide a coherent methodology for selection, although that approach does not significantly contribute to mapping of important traits and pre-selection of superior new hybrid rootstocks.…”
Section: Discussionmentioning
confidence: 99%
“…Work has been conducted over many years at several institutions to develop and evaluate superior new citrus rootstock cultivars, including at the United States Department of Agriculture (USDA) ( Wutscher and Bowman, 1999 ; Bowman and Rouse, 2006 ; Bowman et al., 2016b , Bowman et al, 2021 ), University of Florida ( Castle, 2010 ; Grosser et al., 2016 ; Grosser et al., 2020 ; Kunwar et al., 2021 ), University of California ( Bitters, 1986 ; Roose et al., 1989 ), Valencian Institute of Agricultural Research (IVIA) in Spain ( Forner-Giner et al., 2003 ; Forner-Giner et al., 2014 ; Martínez-Cuenca et al., 2016 ), CRA-Research Center for Citriculture and Mediterranean Crops (CRA-ACM; CREA) in Italy ( Russo and Reforgiato Recupero, 1984 ; Reforgiato Recupero et al., 2009 ), and in Brazil under the Brazilian Agricultural Research Corporation (EMBRAPA), The Sylvio Moreira Citrus Culture Center, Fundecitrus-IDR-Paraná, and University of São Paulo ( Cantuarias-Avilés et al., 2010 ; Costa et al., 2020a ; Costa et al., 2020b ; Soratto et al., 2020 ; Domingues et al., 2021 ). These efforts have involved a combination of testing rootstock clones already in existence (including those imported from other regions) and creating new clones by sexual hybridization between two parental species.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the Mulamba and Mock selection index is promising in genetic breeding programs for fruit species (Barth et al 2020;Oliveira et al 2018), with advantages such as relative simplicity and ease of application. The ideotype defined here to classify the trees (short plants, with voluminous fruits, and high productivity) considered attributes that are usually sought in other fruit trees (Castro et al 2020;Costa et al 2020), aiming at great aptitude for commercial cultivation and the consumer market. Although CIR was not considered in the selection index, the 𝑅𝑆 𝐸𝐵𝑉 for this quantitative attribute was -1.76 %, while the response to 𝑅𝑆 𝐸𝐺𝑉 was 1.84%.…”
Section: Discussionmentioning
confidence: 99%